APPLICATION OF THE WWW.DEUTSCH-TO-GO.DE WEBSITE FOR LISTENING SKILL TRAINING STUDENTS CLASS XII MIPA 7 SMAN 1 WONOAYU - Rahmaputri, Fadia Nanda; Indriwardhani, Sri Prameswari (Universitas Negeri Malang, 2024)
The website deutsch-to-go.de is a platform that makes learning German easier, particularly when it comes to online grammatik, vocabulary (Wortschatz), and listening skills practice. This study intends to describe how XII Mipa 7 SMAN 1 Wonoayu students utilize the www.deutsch-to-go.de website to improve their listening skills and to learn what the students' reactions are to using the website. This study employed Discovery Learning K–13 as its learning model. Alltag, with Tage as a subtheme, serves as the research's theme. The selection of the learning paradigm is predicated on the use of Discovery Learning in German language instruction at SMAN 1 Wonoayu. On the other hand, themes that have been covered in learning activities and the language levels chosen are determined by the proficiency of XII MIPA 7 students, who are still at the A2 level. The descriptive qualitative research method was employed in this study. The research tools utilized in this study are Google Form-shared observation and questionnaire sheets. The thirty-six pupils in class XII MIPA 7 SMAN 1 Wonoayu served as the research's data source. Findings from observations indicate that using www.deutsch-to-go.de to practice listening skills at XII MIPA 7 SMAN 1 Wonoayu is enjoyable and conducive. The www.deutsch-to-go.de website is simple to use and access, according to the questionnaire's results. Students struggled with the project since they couldn't understand the website's questions, but this was fixed by gradually going over the content again. Students also mentioned that the website is intriguing since it offers practice questions, a wide range of resources, and graphics, which makes some of them desire to utilize it again for the upcoming learning activities.